Sexual Harassment: A barrier to Girls Education - Rachmah Ida; Javaid Aslam; Fikry Zahria Emeraldien; Anbreen Yasin Khan (Universitas Pendidikan Ganesha, 2022)
There are several instances where inequality is shown against women. Education is one sector where the enrollment of women is far less than the enrollment of men. While there are many factors behind it, the current research will look at one of the least researched phenomena of sexual harassment as the cause behind the lack of registration. The issue of sexual harassment is the least studied in Muslim countries. The purpose of this research is to investigate the impact of patriarchal social norms, long distance to school, the presence of female teachers, and sexual harassment as factors causing the enrollment of girls. This type of research is quantitative. The sample for this study was 200 respondents collected through a multistage sampling technique from eight rural locations. The methods used in collecting data are observation and questionnaires. The instrument used in collecting data is a questionnaire sheet. The technique used for data analysis is descriptive qualitative and quantitative analysis. The study results show that society plus culture, especially in rural areas, causes low literacy in girls. These social and cultural boundaries create obstacles for women in social action. As a result, most girls are confined to the confines of their homes. The majority of respondents said that traditional cultural values influenced girls' education. The community does not agree to send their daughters to school to work because of the unsafe environment.